2013
DOI: 10.5194/acp-13-7321-2013
|View full text |Cite
|
Sign up to set email alerts
|

Ozone photochemistry in boreal biomass burning plumes

Abstract: We present an analysis of ozone (O3) photochemistry observed by aircraft measurements of boreal biomass burning plumes over eastern Canada in the summer of 2011. Measurements of O3 and a number of key chemical species associated with O3 photochemistry, including non-methane hydrocarbons (NMHCs), nitrogen oxides (NOx) and total nitrogen containing species (NOy), were made from the UK FAAM BAe-146 research aircraft as part of the "quantifying the impact of B… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
70
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 77 publications
11
70
1
Order By: Relevance
“…However, CO concentrations are also diminished and consistently below 100 ppb, relative to an average of 200 ppb for aged plumes, while OA concentrations are comparable to levels in higher altitude, flaming-type plumes (∼ 20 µg m −3 ). These trends, which diverge from the expected characteristics for emissions of this origin, are further compounded by high O 3 / CO (> 0.2), indicative of an elevated level of oxygenation and photochemical activity (Mason et al, 2001;Parrington et al, 2013). Formation of SOA from biogenic precursors has previously been observed in the forests of Ontario (Slowik et al, 2010).…”
Section: Aging As a Driver For Plume Variabilitymentioning
confidence: 97%
See 1 more Smart Citation
“…However, CO concentrations are also diminished and consistently below 100 ppb, relative to an average of 200 ppb for aged plumes, while OA concentrations are comparable to levels in higher altitude, flaming-type plumes (∼ 20 µg m −3 ). These trends, which diverge from the expected characteristics for emissions of this origin, are further compounded by high O 3 / CO (> 0.2), indicative of an elevated level of oxygenation and photochemical activity (Mason et al, 2001;Parrington et al, 2013). Formation of SOA from biogenic precursors has previously been observed in the forests of Ontario (Slowik et al, 2010).…”
Section: Aging As a Driver For Plume Variabilitymentioning
confidence: 97%
“…Research flights primarily originated from Halifax and largely involved surveying areas adjacent to the Gulf of St. Lawrence and the North Atlantic. A predominant source region in northwestern Ontario (approximately 52.5 • N, 93.5 • W) has been identified for the majority of plumes sampled throughout BORTAS, although more disperse fires were also active in northern Alberta and the Northwest Territories Parrington et al, 2013). As the majority of plumes from fires in this region were encountered at a distance of several thousand kilometres downwind, emissions would have undergone substantial processing prior to sampling, with estimated photochemical ages between 1-11 days.…”
Section: Introductionmentioning
confidence: 99%
“…Most observations have shown that ozone is produced from fire emissions, yet some have reported no ozone enhancement or even ozone depletion in fire plumes depending on plume age, effects of co-emitted aerosols, and mixing with urban pollution (Singh et al, 2010(Singh et al, , 2012Jaffe and Wigder, 2012;Parrington et al, 2013;Baylon et al, 2015). Observations of ozone enhancements in fire plumes indicated by the O 3 /CO enhancement ratio show a wide range of -0.1 to 0.9 nmol mol -1 /nmol mol -1 , and tend to increase with plume age (Jaffe and Wigder, 2012;Wigder et al, 2013).…”
Section: Biomass Burning Emissionsmentioning
confidence: 99%
“…31). Parrington et al (2013) showed that ozone formation increases with plume age. They used NMHC ratios (extensively described for this BORTAS campaign in to estimate photochemical ages of the observed biomass burning plumes between 0 and 10 days.…”
Section: Biomass Burningmentioning
confidence: 99%